(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
In this study, essential oils from different organs of Satureja bachtiarica Bunge were obtained by hydro-distillation. Quality and quantity of chemical composition of essential oils were determined by capillary gas chromatography and using gas-chromatography and mass spectrometric detection. The numbers of compounds were identified in the essential oils of leaves; stem and aerial parts were 45, 39 and 35, respectively. Also, carvacrol was the main component found in essential oils from leaves (39.3%), stem (39.4%) and aerial parts (67.88%) of S. bachtiarica in flowering stage. In addition, results showed that there were some different in compositions of the essential oils of different parts of S. bachtiarica and there are some minor components in each oil that are not present in the others parts. In addition chemical analysis of essential oils obtained from leaves and stem of S. bachtiarica were rich in oxygenated monoterepens (55.64% and 67.53%) while oxygenated monoterepen (77.22%) were the main class of compounds in the essential oils from aerial parts of S. bachtiarica. Results of this study showed that the essential oils from different organs of S. bachtiarica have a potential to be used as a new carvacrol source in drug and food industries.